Peran Dinas Perindustrian dan Perdagangan dalam Sarana Mengembangkan IKM di Kabupaten Deli Serdang - Ayu Andini; Wahyu Syarvina (Universitas 45 Surabaya, 2024)
The Department of Industry and Trade (Disperindag) of Deli Serdang Regency is a government agency whose one of its duties is to record the existence of Small and Medium Industries (IKM). The role of the Department of Industry and Trade of the Deli Serdang Regency is very much needed in developing IKM in the Deli Serdang Regency. The existence of SMEs has a very important function in improving the economy both in the regions. This study aims to identify and analyze the role of the Department of Industry and Trade of Deli Serdang Regency in developing small and medium-sized businesses in Deli Serdang Regency. The type of research used is survey research, the primary data source is all employees of the Industry and Trade Office, the Sub-Department of Facilities and Infrastructure and Industrial Empowerment, totaling 10 people. Data analysis was carried out in a quantitative descriptive manner. The results of the study show that the role of the Department of Industry and Trade is very helpful to the local community by fostering small and medium industries, controlling the development of small and medium industries and realizing the development of small and medium industries in a better direction.